Drowned Town - Waldrop, Jayne Moore (Book collections on Project MUSE., 2021)
"They had been told their sacrifice was for the public good. They were never told how much they would miss it, or for how long. Drowned Town explores the multigenerational impact caused by the loss of home and illuminates the joys and sorrows of a group of people bound by western Kentucky's Land Between the Lakes and the lakes that lie on either side of it. The linked stories are rooted in a landscape forever altered by the impoundment of the Tennessee and Cumberland rivers and the taking of property under the power of eminent domain to create the national recreation area on a narrow strip of land running between the lakes. The massive federal land and water projects that came in quick succession were designed to serve the public interest by providing hydroelectric power, flood control, and economic progress for the region, but at great sacrifice for those who gave up their homes, livelihoods, towns and history in the process. The narrative follows two women characters whose lives are shaped by their friendship and connection to the place, and goes back and forth in time to show how the creation of the lakes both healed and hurt the people connected to them. In the process, the stories focus on the importance of sisterhood and family, both blood and created, and how we cannot separate ourselves from our places in the world"--